X-ray Induced Morpho-physicochemical Divergence in Peanut (Arachis hypogaea L.) Mutants - Mariom Mitu; Md. Kawsar Alam Nadim; Md. Shamiul Haque; A.S.M Hasibuzzaman; Sakina Khanam; Md. Abul Kalam Azad (International Journal on Food, Agriculture and Natural Resources, 2022)
Peanut is a crucial source of edible oil and nutrients. Five peanut genotypes' yield and quality parameters were assessed to select superior genotypes. The experiment was conducted in Bangladesh Institute of Nuclear Agriculture HQ's experimental field, Mymensingh-2202. Correlation study identified significant positive correlation of pods plant-1, kernel weight and shelling % with pod yield. Considering yield and oil content, the genotype B6/282/80 performed the best, with a yield of 2.25t/ha and 54.6% edible oil content. Oleic acid/Linoleic acid (O/L) ratio and iodine content were also higher in B6/282/80, followed by B6/282/63. RM-Kha-19 contains the maximum amount of protein (32.42%), while crude fibre and carbohydrate content were the highest in Binachinabadam-4. B6/282/64 possessed the maximum moisture (6.2%), while B6/282/80 had the highest amount of ash (2.35%). The principal component analysis identified that the first two principal components explained about 74.93% of the total variation. Biplot revealed that B, crude fibre, and ash content were higher in Binachinabadam-4. The genotype B6/282/63 was superior in K, S, Fe, moisture, and carbohydrate content. Genotype B6/282/80 was the best genotype for P content. Ca, Cu, N, Mg and Zn content was higher in the RM-KHA-19 genotype. Combining all the energy sources, the genotype B6/282/80 provides the maximum energy, i.e., 628.4 Kcal/100g. Considering the studied traits, the B6/282/80 has the potential to be set on a multilocational trial for the detection of stability as a new variety.